Construction safety training using immersive virtual reality - Sacks, Rafael; Perlman, Amotz; Barak, Ronen (Construction management and economics, 2013)
Construction workers' ability to identify and assess risks is acquired through training and experience and is among the key factors that determine their behaviour and thus their safety. Yet researchers have questioned the effectiveness of conventional safety training. This research tested the hypotheses that safety training in a virtual reality (VR) construction site would be feasible and more effective, in terms of workers' learning and recall in identifying and assessing construction safety risks, than would equivalent training using conventional methods. Sixty-six subjects were provided training in construction safety and their safety knowledge was tested prior to the training, immediately afterward, and one month later. Half of the subjects received traditional classroom training with visual aids; the other half were trained using a 3D immersive VR power-wall. Significant advantage was found for VR training for stone cladding work and for cast-in-situ concrete work, but not for general site safety. VR training was more effective in terms of maintaining trainees' attention and concentration. Training with VR was more effective over time, especially in the context of cast-in-situ concrete works. Given the need for improved training and the advantages of training using VR, incorporation of VR in construction safety training is strongly recommended.